2022
DOI: 10.3390/ijerph19020763
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stressors and Access to COVID-19 Resources among Commuting and Residential Hispanic/Latino Farmworkers in a US-Mexico Border Region

Abstract: Hispanic/Latino and migrant workers experience high degrees of occupational stress, constitute most of California’s agricultural workforce, and were among the most impacted populations by the COVID-19 pandemic. However, relatively little is known about the occupational stress experienced by farmworkers who commute daily between the US and Mexico. Occupational stress is considered an imbalance between the demands at work and the capabilities to respond in the context of the workforce. The goal of this study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…This is supported by Gonzalez et al (2021) , who found that 59% of adults in California immigrant families were very or somewhat worried about exposure to COVID-19 at their place of employment, compared to 45% of adults in non-immigrant families. The study results support findings from our quantitative study of agricultural workers in Imperial Valley ( Keeney et al 2022a , 2022b ), which found that foreign-born workers, regardless of citizenship status or current country of residence, experienced higher levels of stress. Although interviewees did discuss a wide variety of available resources and programs aimed to assist them during the pandemic, they did not mention the ‘Housing for the Harvest’ program as an option to help protect their families by quarantining away from them.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is supported by Gonzalez et al (2021) , who found that 59% of adults in California immigrant families were very or somewhat worried about exposure to COVID-19 at their place of employment, compared to 45% of adults in non-immigrant families. The study results support findings from our quantitative study of agricultural workers in Imperial Valley ( Keeney et al 2022a , 2022b ), which found that foreign-born workers, regardless of citizenship status or current country of residence, experienced higher levels of stress. Although interviewees did discuss a wide variety of available resources and programs aimed to assist them during the pandemic, they did not mention the ‘Housing for the Harvest’ program as an option to help protect their families by quarantining away from them.…”
Section: Discussionsupporting
confidence: 87%
“…The COVID-19 pandemic has exacerbated the already existing burdens and stressors of agricultural workers ( Keeney et al, 2022a ; COVID-19 Farmworker Study, 2020 ; Kerwin and Warren 2020 ; Reid et al, 2020 ; Haley et al, 2020 ). To improve the quality of lives of these critical workers, much work is still needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, death by suicide among foreign-born workers almost doubled from 2017 to 2018, in a non-pandemic year [2]. Increased mental health challenges and COVID-19 related stress associated with the loss of family members, reduction of income and work, and lack of personal protective equipment have been found among Hispanic/Latino, foreign-born farmworkers [3][4][5]. Studies have indicated that most people who die by suicide have a mental or emotional disorder, and depression and anxiety are associated with suicide attempts [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Rural CBOs must begin developing partnerships to collaborate and coordinate information dissemination, education, and outreach efforts related to mental health and wellness toward farming populations. Trusted community collaborations have been found to play a pivotal role in registering Hispanic/Latino farmworkers for the COVID-19 vaccine (Keeney et al, 2022). Establishing and maintaining these collaborations could effectively disseminate vital public health information to a vulnerable and underserved population, often with high medical mistrust.…”
Section: Discussionmentioning
confidence: 99%